(untitled) (Journal of Economic Research & Business Administration, 2015)
In this article, the authors investigate the problem of students health Northern region of Kazakhstan, given the statistical analysis of dental disease, anemia, obesity, and Digestive Diseases in the areas of Akmola region and Kokshetau, shows the results of a sociological survey on the state of health of schoolchildren in Petropavlovsk. Based on identify the main causes of schoolchildren’s diseases, authors propose to change relation to organization school food towards a variety range used food by means of broader inclusion in a dietary structure, first of all products of plant origin such vegetables and root vegetables as celery, pumpkin, ginger, artichokes, beans, processed products of vegetable raw materials: frozen mixed vegetables, germinated seeds, canned vegetables.